2013
DOI: 10.1007/s00436-013-3676-9
|View full text |Cite
|
Sign up to set email alerts
|

Solanum trilobatum extract-mediated synthesis of titanium dioxide nanoparticles to control Pediculus humanus capitis, Hyalomma anatolicum anatolicum and Anopheles subpictus

Abstract: Titanium dioxide nanoparticles (TiO2 NPs) are widely used in paints, printing ink, rubber, paper, cosmetics, sunscreens, car materials, cleaning air products, industrial photocatalytic processes, and decomposing organic matters in wastewater due to their unique physical, chemical, and biological properties. The present study was conducted to assess the antiparasitic efficacies of synthesized TiO2 NPs utilizing leaf aqueous extract of Solanum trilobatum against the adult head louse, Pediculus humanus capitis De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(25 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…The reaction mixtures start vigorously when a precursor TiO 2 salt is adulterated with plant extract, color change indicates the first sign of synthesis that can then be confirmed afterwards by spectroscopic techniques. Several color indicators have been reported ranging from light green to dark green in the formation of TiO 2 NPs Dobrucka (13), Rajakumar et al (23), Rajakumar et al (24).…”
Section: Plantsmentioning
confidence: 99%
“…The reaction mixtures start vigorously when a precursor TiO 2 salt is adulterated with plant extract, color change indicates the first sign of synthesis that can then be confirmed afterwards by spectroscopic techniques. Several color indicators have been reported ranging from light green to dark green in the formation of TiO 2 NPs Dobrucka (13), Rajakumar et al (23), Rajakumar et al (24).…”
Section: Plantsmentioning
confidence: 99%
“…22 Several reports are available for the synthesis of TiO 2 NPs using plant/leaf extracts of Nyctanthes arbor-tristis, Solanum trilobatum, Annona squamosa, Catharanthus roseus, Calotropis gigantea, and Jatropha curcas. [23][24][25][26][27][28] In the present study, Artocarpus heterophyllus leaf extract was used as a reducing and surface modifying agent. To the best of our knowledge, this is the rst report where Artocarpus heterophyllus leaf aqueous extract was used as a reducing and surface modifying agent in the synthesis of TiO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Velayutham et al (2012) reported the antiparasitic activities of synthesized TiO 2 NPs utilizing leaf aqueous extract of Catharanthus roseus against the adults of Hippobosca maculata and Bovicola ovis. The antiparasitic efficacies of synthesized TiO 2 NPs utilizing leaf aqueous extract of Solanum trilobatum against the adult head louse, Pediculus humanus capitis, larvae of cattle tick Hyalomma anatolicum anatolicums, and fourth instar larvae of malaria vector A. subpictus were evaluated (Rajakumar et al 2014).…”
Section: Introductionmentioning
confidence: 99%